PENGARUH DEMOKRASI TERHADAP PERDAGANGAN INTERNASIONAL INDONESIA DENGAN NEGARA-NEGARA ASEAN - Tucunan, Sharon Nabila Jelita Lophina; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024, 2024)
Democracy is one of the important roles to support trade between countries with one another. The role of the political system in a country, whether democratic or autocratic, has important implications for all economic decisions made by the government. The interaction of economic development with democracy is very influential for a country. The purpose of this study was to determine the effect of democracy on international trade, especially in Indonesia with countries in ASEAN. This research was conducted in Indonesia with ASEAN countries, namely Malaysia, the Philippines, Singapore, Thailand, Myanmar, Cambodia, Laos, and Vietnam. Samples were collected online through the official website of the Central Statistics Agency (BPS), the World Bank, and other supporting sources. The analysis technique used is descriptive statistical technique. Based on the results of the analysis, it was found that democracy has a positive effect on Indonesia's international trade with countries in ASEAN.